1984
DOI: 10.1523/jneurosci.04-09-02191.1984
|View full text |Cite
|
Sign up to set email alerts
|

Afferent specific localization of muscarinic acetylcholine receptors in cingulate cortex

Abstract: The laminar distribution of acetylcholine receptors in rat cingulate cortex and their localization to axons of neurons in the anterior thalamic nuclei (ATN) were evaluated with the muscarinic antagonist[3H]propylbenzilylcholine mustard (PrBCM) in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Second, does transneuronal degeneration account for alterations subsequent to deafferentation lesions (Hattori and Fibiger, 1982)? As noted previously (Vogt, 1984), 2 peaks in PrBCM binding in cingulate cortex were reduced by 40-50% following ATN or undercut lesions, and they remained after ibotenic acid lesions. We have explored ibotenic acid-ablated cortex electron microscopically and found that, although neurons are virtually nonexistent, axon terminals did remain (unpublished observations).…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…Second, does transneuronal degeneration account for alterations subsequent to deafferentation lesions (Hattori and Fibiger, 1982)? As noted previously (Vogt, 1984), 2 peaks in PrBCM binding in cingulate cortex were reduced by 40-50% following ATN or undercut lesions, and they remained after ibotenic acid lesions. We have explored ibotenic acid-ablated cortex electron microscopically and found that, although neurons are virtually nonexistent, axon terminals did remain (unpublished observations).…”
Section: Methodssupporting
confidence: 81%
“…Peak layer Ia binding was usually reduced by 40-50% for the former ligands. Although incomplete ATN lesions could account for some variation, complete undercut lesions also failed to abolish the layer Ia peak in PrBCM binding (Vogt, 1984). In addition, ibotenic acid lesions always reduced peak binding of PrBCM and OXO/PZ in layers Ia and IV by about 50%.…”
Section: Localization Of Dendritic M Receptorsmentioning
confidence: 91%
See 2 more Smart Citations
“…Figure 13 shows high expression of AChE in layer Ia where AV axons terminate and greater than 50% loss of this activity following thalamic lesions (right side of Fig. 13 "Ablation"; Vogt, 1984).…”
Section: Thalamic Afferentsmentioning
confidence: 99%